Effect of Neurodynamic Slider Technique Combined with Conventional Therapy and Conventional Therapy Alone in Sciatica: A Comparative Study (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2021)
Background: Functional activity is an important aspect of normal human function. Limited functionalactivities due to in sciatica have been shown to predispose a person to several restrictions in functionand significantly affect the normal daily life.Objective: To determine and compare the effectiveness of Neurodynamic Slider Technique (NST) withconventional therapy (CT) and conventional therapy alone in sciatica for improving functional abilityand pain.Method: 40 subjects with sciatica were allocated into two groups (20 subjects in each group). Theoutcome measure used was Oswestry Disability Index (ODI) and Visual Analogue Scale (VAS).Subjects of group A were treated with Conventional therapy only, whereas the subjects of group B weretreated with Neurodynamic slider technique. For both the groups, the technique was performed threetimes a week for a total treatment period of four weeks.Results: The results demonstrated significant improvement in functional ability for subjects of group Bwhen compared with those of group A (P
Keywords: Sciatica, Low Back Pain, Functional ability, Neurodynamic slider technique, Conventional therapy, VAS.